Brain-aging related protein expression and imaging characteristics of mice exposed to chronic hypoxia at high altitude - Cao, Yaxin; Cao, Shundao; Ge, Ri-Li; Bao, Haihua; Mou, Yalin; Ji, Weizhong (Frontiers in Aging Neuroscience, 2023)
Objective: To determine changes in protein expression related to brain aging and imaging features in mice after chronic hypoxia exposure at high altitude. Method: A total of 24 healthy 4-week-old mice were randomly divided into high altitude hypoxia (HH) and plain control (PC) groups (n=8 per group). HH mice were transported from Xi 'an (450 m above sea level) to Maduo (4300 m ) while PC mice were raised in Xi 'an. After 6 months. All mice underwent multimodal magnetic resonance imaging. Next, brain slices were prepared and Nissl staining was used to observe morphological changes in neurons. Ultrastructural changes in neurons were observed by transmission electron microscopy. Expression changes of Caspase-3, klotho, P16, P21, and P53 were detected by real-time PCR (RT-PCR) and Western blot.The number of neuronal Nissl bodies was significantly decreased in the HH group . Some hippocampal and frontal cortical neurons were apoptotic, the nuclei were wrinkled. The HH group showed elevated expression of caspase-3 , P16 , P21 , and P53 mRNA . Expression of Klotho mRNA in the frontal cortex was significantly decreased. Western blot results showed that caspase-3 protein expression of the HH group was increased . Moreover, there was decreased Klotho protein expression and significantly increased P-P53 expression. Compared with the PC group, expression of P16 protein was increased and the gray matter (GM) volume in the left visceral area. Furthermore, the amplitude of low frequency fluctuation was decreased in multiple brain regions, but increased in the GM layer of the left superior colliculus. Regional homogeneity was decreased in the bilateral olfactory regions, but increased in the left bed nucleus. Functional connectivity (FC) between the bilateral caudate nucleus and thalamus, cingulate gyrus, and hippocampus was weakened. The fractional anisotropy value of the left hippocampus was decreased in the HH group. the HH group showed significantly increased inner diameters of the bilateral common carotid artery and left internal carotid artery. Taken together, our findings show that chronic hypoxia exposure at high altitude may promote abnormal expression of related proteins, changing the structure and function of brain. These changes may contribute to brain aging.